A Study of Self- Medication Uses without a Prescription among Iraqi Patients in Baghdad City - Shatha Saadi Mohammed; Ahmed Mohammed Jasim Shlash (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Medicines are those chemical compounds which consist of a single substance or more and areobtained through natural (plant or animal), as well as industrial methods, by chemical reactions that utilizedin the treatment of diseases that can infect human and animals or alleviate illness, prevention or diagnosing.Self-medication is the unwanted medical use of prescription and / or over-the-counter drugs. These practiceshave become an encouraging global form of self-care when it comes to minor ailments. Well it is not limitedto over-the-counter medicines. This also includes the use of prescription medications such as antibiotics.Objective: This study explores the extent of a widespread phenomenon of medicines usage without a doctorprescription, and studied the self-medication practices reasons among patients in the city of Baghdad.Methods: A cross-sectional descriptive study was conducted by questionnaires were distributed randomlyto 300 adults in different age group, sex and level of education at PHC in Baghdad city.Result: In this study, findings depict that the (34.3%) of study male participants are aged (30-39) years old.In regarding with education, thirty-four percent are primary school graduated and work a housewife residentin rural areas. Also, the (53 %), (12.3%) respectively take drugs in the last months for flu. The (64.7%) ofdrugs was prescribed by physician and (35.3%) of drug take without prescription because (16.3%) of themnot have access to physician care. The source of drugs supplies, the (31.7%) take it from others source and(38.3%) of information on the use of these drugs was obtained from physicians. The most common types ofdrugs used without prescription the result indicated that (39.0) was antibiotics and (53.3%) of sample notcommitment by dose, Reading instructions & advertence with complication. Also the (73%) of sample don’tuses or depending upon herbs.Conclusion & Recommendations: The continued use of medications without a prescription is an alarmingproblem in the country of Iraq. The prevalence of self-medication management is high in Middle Easterncountries and is often associated with inappropriate drug use. Therefore, it is necessary to understand therelationship between the various factors that favor the management of self-medication and to evaluate theevolving trends to help us develop strategies to reduce the health risks associated with drugs among thepeople of the Middle East.The recommendations included the imposition of regulatory measures that restrict access to prescriptionmedications only in countries where antibiotics are available over the counter. Another recommendation,which has emerged in several studies, is to improve the use of media campaigns to effectively guide publiceducation programs.